Deliberation and Development: Rethinking the Role of Voice and Collective Action in Unequal Societies - and Heller, Patrick; Rao, Vijayendra (World Bank Publications, 2015)
This book marries two fields that rarely converse with one another:deliberative democracy and development studies. The study ofdeliberation—which explores normative and practical questions aroundgroup-based decision making through discussion or debate—has emergedas a critical area of study over the past two decades. Concurrently, the fieldof development has seen a spurt of interest in community-led developmentand participation premised on the ability of groups to arrive at decisionsand manage resources via a process of discussion and debate. Despite thegrowing interest in both fields, they have rarely engaged with one another.This book, which brings together new essays by some of the leading scholarsin the field, deepens our understanding of participatory decision makingin developing countries while initiating a new field of study for scholarsof deliberation. In the process, it sheds light on how to best design andimplement policies to strengthen the role of participation in development.